Kontribusi Frekuensi Belajar Dan Keaktifan BerorganisasiTerhadap Kesulitan Belajar Akuntansi Perpajakan Pada Mahasiswa Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan 2012/2013 - Adiyati, Rukmana; , Drs. M. Yahya, M.Si (2015)
Difficulty learning a lot of things perceived by learners when faced with a lot of courses that must be understood and controlled. Learning difficulties should be identified so that learners are able to learn how to fix them, in this case the frequency of learning and organize the activity can help reduce the learning difficulties of students in particular courses Tax Accounting. The purpose of this study to find out: 1. Contributions frequency of learning on learning difficulties Tax Accounting courses. 2. Contributions liveliness organize against learning difficulties Tax Accounting courses. 3. The significant contribution between the frequency and activity of organizational learning together against difficulties learning courses Tax Accounting, Accounting Education Student Guidance and Counseling UMS force 2012/2013. This research was conducted at the Faculty of Education, University of Muhammadiyah Surakarta, Pabelan, Kartosuro. The population in this study were all students of 2012/2013 were active in the organization amounted to 73 students, sample of 58 students who are active in the HMP, the technique used is non probability sampling-sampling purposive. The technique of collecting data using questionnaires and documentation. Data were analyzed using multiple linear regression analysis, F test, t-test, R2, the calculation of the relative contribution and effective contribution. The results of this study are: 1. Frequency of learning contributes to learning difficulties, based on the results of the ttest analysis that t count > ttable, is 5,340 > 2,004 and significance < 0,05, that is 0,000, and the effective contribution of 26,3%. 2. The active participation contribute to organizational learning difficulties, the results of the ttest analysis that tcount > ttable, 5,001 > 2,004 and the significance value < 0,05, namely 0,006, the effective contribution of 7,4%. 3. Frequency of learning and organize the activity contribute together to the learning difficulties, the results of the F test analysis the gain of F > Ftable, is 28,519 > 3,165 and significance value < 0,05, namely 0,000. 4. The coefficient of determination obtained a value of 0,337 or contributions given frequency and activity of organizational learning for learning disabilities at 33,7%, while 66.3% are influenced by other factors.